Estudo da influência dos raios x de freamento produzidos pelas partículas beta do ítrio-90 em sistema SPECT utilizando simulação Monte Carlo - Orejuela, Carlos Omar Pastrana (2018)
In Nuclear Medicine Yttrium-90 ( 90Y ) is one of the most widely used radiopharmaceuticals. However, the energetic characteristics of this pure beta emitter constitute a difficulty for dose planning using SPECT images. The objective of this work is to study the influence of the bremsstrahlung X-rays produced by the beta particles emitted by 90Y for SPECT image acquisition, using the Monte Carlo code MCNPX. Several simulations were carried out to evaluate aspects that could affect the quality of the SPECT image: collimator type, collimator-source distance, geometry of the system and material composition. Point sources of 90Y were simulated in various materials; cylindrical simulators filled with yttrium-labeled hydroxyapatite solution (HA−90Y ); the distribution of the energy deposited by the photons in the detector crystal NaI (Tl) for cylindrical and spherical sources is also studied using the tally TMESH available in code MCNP. The Monte Carlo simulation was validated by comparing the spectral distribution of the bremsstrahlung X-rays of the β particles of 90Y in the NaI(Tl) crystal detector with the spectrum obtained experimentally by the SPECT system, installed in the Department of Nuclear Medicine of the University Hospital Clementino Fraga Filho (HUCFF/UFRJ). The study allowed to correlate the produced, absorbed and escaping braking photons of the analyzed media with the energy deposited by the electrons in the material. The collimators that generate the best spatial resolution and the optimal source-collimator distance for each of the radionuclides simulated in this work were determined.